2023
DOI: 10.1038/s41598-023-37871-x
|View full text |Cite
|
Sign up to set email alerts
|

Preterm births prevalence during the COVID-19 pandemic in Brazil: results from the national database

Charles M’poca Charles,
Luiz Alves Souza Neto,
Camila Ferreira Soares
et al.

Abstract: The SARS-CoV-2 (COVID-19) pandemic impacted the health systems between and within countries, and in the course of the pandemic sexual and reproductive health services were the most disrupted. Findings from high-income settings have reported significant changes in preterm birth prevalence during the pandemic period. To understand the possible effects of the COVID-19 pandemic on preterm birth numbers at the Brazilian national level. We compare the number of preterm deliveries during the COVID-19 pandemic period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Also amongst the included studies we must acknowledge important contextual background differences that can influence the associations we reviewed. In fact, these countries may have distinct reported preterm birth rates, [51][52][53] primary health care and social and school systems that could modify the studied relationships. Due to a high level of heterogeneity between studies and the small sample size used, these factors were not tested for interaction, and we cannot conclude on their effects or their absence of effects.…”
Section: Discussionmentioning
confidence: 99%
“…Also amongst the included studies we must acknowledge important contextual background differences that can influence the associations we reviewed. In fact, these countries may have distinct reported preterm birth rates, [51][52][53] primary health care and social and school systems that could modify the studied relationships. Due to a high level of heterogeneity between studies and the small sample size used, these factors were not tested for interaction, and we cannot conclude on their effects or their absence of effects.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal health is of great interest in all conditions impacted by COVID-19 as it is a proxy indicator of the quality of a country's healthcare services. [4][5][6][7] As the COVID-19 pandemic continued to spread, there was a notable rise in cases of moderate to severe illness among pregnant women, leading to concerns about their susceptibility to infection and potential fatalities. [4][5][6][8][9][10][11] Thus, beyond the fear of the possibility of vertical transmission, special attention was initially given to understanding the direct effects of COVID-19 on maternal health.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the severity of infection during pregnancy was a primary area of concern, especially in women from high-risk groups, such as those with obesity, hypertension, diabetes, and immunosuppression conditions. 1,[6][7][8][9][10][11] In this aspect, a systematic review with meta-analysis including 42,754 infected pregnant patients showed a rapid increase in cesarian sections (c-sections); the mortality trend was not elucidated with a maternal mortality rate of 1.2% and a rise of preterm births. 11 It is important to note that the impact of the pandemic on maternal health transcended the direct effects of individual infections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations